2016
DOI: 10.1016/j.bbrc.2016.05.011
|View full text |Cite
|
Sign up to set email alerts
|

A comparative structural analysis reveals distinctive features of co-factor binding and substrate specificity in plant aldo-keto reductases

Abstract: Plant aldo-keto reductases of the AKR4C subfamily play key roles during stress and are attractive targets for developing stress-tolerant crops. However, these AKR4Cs show little to no activity with previously-envisioned sugar substrates. We hypothesized a structural basis for the distinctive cofactor binding and substrate specificity of these plant enzymes. To test this, we solved the crystal structure of a novel AKR4C subfamily member, the AKR4C7 from maize, in the apo form and in complex with NADP(+). The bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…). For instance, in the plant AKR4 family, specific interactions of a shortened loop 7 that stabilize the closed conformation of the loop were held responsible for the lower cosubstrate affinity and activity of Zm AR in comparison to hAR .…”
Section: Discussionmentioning
confidence: 99%
“…). For instance, in the plant AKR4 family, specific interactions of a shortened loop 7 that stabilize the closed conformation of the loop were held responsible for the lower cosubstrate affinity and activity of Zm AR in comparison to hAR .…”
Section: Discussionmentioning
confidence: 99%
“…ZmAKR4-expressing E. coli showed the highest glyphosate tolerance, as indicated by the detoxification of most of the glyphosate ( Figure 2 A–C). Previous studies revealed that ZmAKR4 preferred the conversion of sorbitol to glucose in the reaction (sorbitol + NADP + ⇄ glucose + NADPH) [ 31 , 41 ]. Therefore, ZmAKR4 appeared to favour using NADP + to oxidize glyphosate, rather than using NADPH to reduce benzaldehyde.…”
Section: Resultsmentioning
confidence: 99%